Effect of Application of Critical-Care Pain Observation Tool in Patients with Decreased Level of Consciousness on Performance of Nurses in Documentation and Reassessment of Pain - Ahmad Ali Asadi Noghabi; Mohammad Gholizadeh Gerdrodbari; Mitra Zolfaghari; Abbas Mehran (Tehran University of Medical Sciences, 2012)
Background & Aim: The presence of pain is a common phenomenon among patients in critical care units. Critically ill patients are often unable to communicate because of illness or sedation so, recognition and assessment of their pain is difficult. In these patients, observational behavioral indices can be used to evaluate pain. The aim of this study was to investigate the effect of application of critical-care pain observation tool in patients with decreased level of consciousness on performance of nurses in documentation and reassessment of pain after palliative intervention. Methods & Materials: In this before and after quasi-experimental study, 106 nurses working in general intensive care units in selected hospitals affiliated to Tehran University of Medical Sciences were selected. First, we examined the nurses&apos performance three times in relation to documentation and reassessment of pain after palliative intervention, position change and suction procedure in patients with decreased level of consciousness using a researcher-made check list. Then, we taught nurses individually, how to use this tool to investigate the pain of patient in a session lasting an hour. A week after the training, the researcher reevaluated performance of trained nurses in relation to documentation and reassessment of pain after palliative intervention in patients with decreased level of consciousness. Finally, those data collected before and after the training of the CPOT to nurses were compared using the Wilcoxon test. Results: Findings showed that the CPOT could not lead to improved nurses&apos function in relation to documentation of pain in the patients records (P=0.209) and recording palliative measures related to pain (P=0.117). However, there were significant statistical differences between nurses&apos function in relation to reassessment of pain after palliative intervention, before and after the training and application of the CPOT. Comparing the mean function scores before and after the intervention, demonstrated that the performance of nurses in this area has been improved after the intervention. Conclusion: The critical-care pain observation tool can increase nurses&apos sensitivity to pain in patients with decreased level of consciousness. It forces the nurses to reassess the pain after palliative intervention. This tool does not motivate in nurses to document pain palliative process. So it is recommended that future studies investigate the impact of this tool on other aspects of pain management, such as diagnosis of pain and using of drugs and non-drug measures.